Posted by Caroline on Wednesday, April 10, 2013 at 12:19am.
12.
3 / 12 = 3 / ( 3 * 4 ) = 1 / 4
5 / 15 = 5 / ( 5 * 3 ) = 1 / 3
( x + 3 / 12 ) / ( 4 x - 5 / 15 ) =
( x + 1 / 4 ) / ( 4 x - 1 / 3 ) =
( 4 x / 4 + 1 / 4 ) / ( 4 x * 3 / 3 - 1 / 3 ) =
[ ( 4 x + 1 ) / 4 ] / [ ( 12 x - 1 ) / 3 ] =
( 4 x + 1 ) * 3 / [ 4 * ( 12 x - 1 ) ] =
( 3 / 4 ) ( 4 x + 1 ) / ( 12 x - 1 ) =
3 * ( 4 x + 1 ) / [ 4 * ( 12 x - 1 ) ] =
( 12 x + 3 ) / ( 48 x + 4 )
14.
( 2 / x ^ 2 + 1 / x ) / ( 4 / x ^ 2 - 1 / x ) =
[ 2 / x ^ 2 + 1 * x / ( x * x ) ] / [ 4 / x ^ 2 - 1 * x / ( x * x ) ] =
( 2 / x ^ 2 + x / x ^ 2 ) / ( 4 / x ^ 2 - x / x ^ 2 ) =
[ ( 2 + x ) / x ^ 2 ] / [ ( 4 - x ) / x ^ 2 ] =
[ x ^ 2 * ( 2 + x ) / x ^ 2 ] / [ x ^ 2 * ( 4 - x ) / x ^ 2 ] =
( 2 + x ) / ( 4 - x )
16.
( 1 / y + 3 / y ^ 2 ) / ( y + 27 / y ^ 2 ) =
[ 1 * y / ( y * y ) + 3 / y ^ 2 ) ] / [ y * y ^ 2 / y ^ 2 + 27 / y ^ 2 ) ] =
( y / y ^ 2 + 3 / y ^ 2 ) / ( y ^ 3 / y ^ 2 + 27 / y ^ 2 ) =
[ ( y + 3 ) / y ^ 2 ] / [ ( y ^ 3 + 27 ) / y ^ 2 ) =
[ y ^ 2 * ( y + 3 ) / y ^ 2 ] / [ y ^ 2 ( y ^ 3 + 27 ) / y ^ 2 ) =
( y + 3 ) / ( y ^ 3 + 27 ) =
( y + 3 ) / [ ( y + 3 ) * ( y ^ 2 - 3 y + 9 ) =
1 / ( y ^ 2 - 3 y + 9 )
12.
(x+3/12)/(4x-5/15)
first reduce those fractions to lowest terms
= (x + 1/4) / (4x - 1/3)
multipy top and bottom by 12 , the LCD
= (12x + 3)/(48x+4) or 3(4x+1)/(4(12x+1) )
14.
(2/x^2 + 1/x)/(4/x^2 - 1/x)
do it the same way, multiply top and bottom by x^2 , the LCD
= (2 + x)/(4 - x)
all done!
try the last one using the same method
Thank you both!